Inovasi Akad Pembiayaan Kartu Kredit pada Perbankan Syariah - Susanto, Dedi; Rayyahun, Annisa; Sukmana, Ahyana Syahila; Lutfi, Mukhtar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Islamic credit cards are one of the innovations in the Islamic financial system aimed at providing non-cash transaction facilities while adhering to Islamic principles. This study aims to identify the challenges and issues faced by Islamic banks in developing and implementing Islamic credit card products in Indonesia. The research method used is a literature study with a descriptive qualitative approach, referring to academic literature, fatwas from the National Sharia Council (DSN-MUI), and banking regulations. The results show that Islamic banks face several key challenges, including limited public understanding of sharia-based contracts, the need for adequate supporting technology systems, and intense competition from more widely known conventional credit cards. In addition, limited product innovation and the need for harmonization between sharia regulations and national financial authority policies remain significant obstacles. Therefore, synergy between regulators, industry players, and academics is necessary to strengthen Islamic credit card products through education, sharia financial literacy, and the development of competitive yet sharia-compliant features.